S102. COGNITIVE-BEHAVIORAL SOCIAL SKILLS TRAINING IN YOUTH AT CLINICAL HIGH RISK FOR PSYCHOSIS: QUANTITATIVE AND QUALITATIVE METHODS: FOR IMPLEMENTATION AND FACILITATOR TRAINING. (9th April 2019) - Kelsven, Skylar; Holden, Jason; Devoe, Dan; Addington, Jean; Auther, Andrea; Kali, Brummitt; Cadenhead, Kristin S; Cornblatt, Barbara; Santesteban-Echarri, Olga; Granholm, Eric
Abstract: Background: Few studies have sought to test the impact of psychosocial interventions on functional impairments in adolescents and young adults at clinical high risk (CHR) for psychosis. Moreover, reliable implementation of psychosocial interventions is costly, requiring years of advanced education and specialized training to adequately implement. Cognitive-Behavioral Social Skills Training (CBSST) combines elements of Cognitive Behavior Therapy with Social Skills Training, two evidence-based treatments for schizophrenia. In the current study, an existing CBSST manual was adapted to make content more appropriate for CHR age range and illness severity. The adapted manual was disseminated and implemented across 3 sites. Key changes to the published manual included a focus on normalization and destigmatization of attenuated psychotic symptoms, as well as examples and role plays that are appropriate for a young CHR sample. The aim of the current paper is to describe the manual modifications and present preliminary data demonstrating the success of training and supervision methods in this multi-site randomized controlled trial of CBSST in CHR youth. Case vignettes will demonstrate how CBSST techniques uniquely target functional impairments characteristic of emerging psychosis. Methods: Subjects were eligible if they met criteria for a prodromal syndrome measured by the Scale of Prodromal Syndromes, demonstrated a mild impairment in social or role functioning, and were between the ages of 12–30. Facilitators included bachelor's level or above clinicians and trainees. Facilitator training on CBSST techniques was completed through a combination of in-person trainings and standardized training tapes. All sessions were audio recorded by facilitators. A random selection of recordings were systematically assessed by 2 raters, blinded to all participant data and tape selection procedure. Recordings were rated for CBT fidelity using the Cognitive Therapy Rating Scale for Psychosis (CTS-Psy) and the SST fidelity using the Social Skills Training Fidelity Scale. Recordings and ratings were used in weekly videoconference supervision to iteratively introduce technical modifications between sessions, address procedural errors, and provide facilitators with written feedback to improve fidelity. Weekly supervision served as a platform to discuss treatment manual revisions and effective strategies to engage youth in CBSST techniques. Results: Fourteen audio recordings were evaluated per site. CTS-Psy and SST overall fidelity ratings were consistent across sites ([mean±SD] Site 1=43.6 ±5.2, Site 2=42.6±3.0, and Site 3=41.9±2.8). There were no site differences on total general skill (Site 1=22.6 ±2.3, Site 2=20.7±1.8, and Site 3=21.3±2.1) nor CBSST technical skill (Site 1=20.9±3.4, Site 2=21.9±2.5, and Site 3=20.6±2.1) ratings. Discussion: Overall fidelity ratings were above the "adequate" range (>30). Thus, quantitatively, a high level of fidelity was achieved through this model of training and supervision. Qualitatively, case vignettes yield anecdotal evidence that CBSST provides a unique set of techniques, easily administered by bachelor's level or above providers, that target functional impairments specific to CHR youth. Taken together, these results provide preliminary evidence that CBSST can be reliably implemented with high fidelity and low cost with target engagement of functional impairment in CHR youth.